Process developed by IITA researchers in Nigeria maximizes private sector production of Aflasafe products (biocontrol products) for commercial use in Senegal, Tanzania, and Nigeria benefiting 12 countries across the African continent - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Various biocontrol products under the tradename Aflasafe are now available across Africa. IITA researchers developed an efficient process for producing high-quality dry spores at IITA Ibadan to supply licensed Aflasafe manufacturers at a cost. The manufacturers only need to combine the dry spores with polymer, dye, and water and coat that suspension onto sorghum to make Aflasafe, a process as simple as making instant coffee. In effect, the technology makes it easier for the private sector to manufacture Aflasafe.